Global prevalence and etio-pathogenesis of autism: a review - Amaravadi, Divya; Muchumari, Bharathi; Firdous, Athika (International Journal of Research in Medical Sciences, 2025)
Autism spectrum disorder (ASD) is a complicated neurobehavioral disorder, characterized by lack of social communication, presence of restricted and repetitive behaviors and lack of verbal development. The condition is believed to stem from cerebral malfunctioning resulting from a complex interplay of environmental, genetic and epigenetic variables. The level and number of symptoms vary from individual to individual and hence the clinical findings cannot be generalized. Prevalence of ASD has risen over the years which is possibly due to increased diagnosis, reporting and awareness. Autistic individuals are observed to have certain physiological challenges as abnormalities in the gut-brain axis with a focus on gut dysbiosis. This current review was prepared using PubMed, Google Scholar and other sources. It presents data on the primary streams about the etio-pathogenesis and global prevalence of ASD. However, it is observed that there is no specific cure for ASD. Timely intervention results in significant enhancements in social communication abilities, cognitive and adaptive functions.